Principles of integrated marketing communications : an eEvidence-based approach - Ang, Lawrence (Cambridge : Cambridge University Press, 2021)
Marketing in the digital age poses major challenges for traditional and established practices of communication. To help readers meet these challenges Principles of Integrated Marketing Communications: An Evidence-based Approach provides a comprehensive foundation to the principles and practices of integrated marketing communications (IMC). It examines a variety of traditional and digital channels used by professionals to create wide-reaching and effective campaigns that are adapted for the aims of their organisations. This edition has been thoroughly revised and each chapter includes: case studies of significant and award-winning campaigns from both Australian and international brands that illustrate the application of explored concepts; discussion and case study questions that enable readers to critically evaluate concepts and campaigns; a managerial application section that illustrates how concepts can be applied effectively in a real situation; a 'further thinking' section that expands knowledge of advanced concepts and challenges readers to think more broadly about IMC.
Title from publisher's bibliographic system (viewed on 04 Mar 2021).
Keywords: Communication in marketing; Marketing -- Technological innovations